Implementation of cloud service platform for monitoring charging facility status of electric vehicle based on MQTT. (2nd June 2023) - Li, Lei; Liu, Weidong; Li, Xiaohui; Yang, Guang; Li, Dan
Aiming at the heterogeneous charging facilities of many manufacturers, the difficulty of communication and information sharing among devices, we design a cloud service platform for monitoring the status of charging facilities of electric vehicles. Firstly, the network topology structure of cloud service platform is given. Then, the logical architecture and functions are designed. The information collection, pushing process and security design of the cloud service platform are described in detail. Finally, the implementation and performance tests of the presented system are carried out. The contribution of this paper is that the proposed message queuing telemetry transport (MQTT)-based internet of things middleware can provide remote parameter configuration and information acquisition functions for charging facilities, shield the underlying hardware devices, realise data interaction between the sensor layer and the upper application, and integration of multi-source information of heterogeneous devices. The research results that the present method has the practical application value.